Human remains unearthed in settlement context from the Late Bronze Age – Early Iron Age (Reinecke BD–HaB3) Northeastern Hungary - Király, Ágnes (Dissertationes Archaeologicae, 2021)
Abstract of PhD thesis submitted in 2020 to the Archaeology Doctoral Programme, Doctoral School of History, Eötvös Loránd University, Budapest under the supervision of Gábor V. Szabó.